Professional-Pedagogical Competence of the Teacher - Olha Orlovska (Pedagogical Discourse, 2012)
The article deals with various approaches to the concept definition „professional-pedagogical competence” and „competence”. Indicators and kinds of professional competence are defined. The basic approaches of scientists to studying of professional competence of the teacher are allocated.